The combined associations of depression and cognitive impairment with functional disability and mortality in older adults: a population-based study from the NHANES 2011–2014 - Han, Shuang; Gao, Yue; Gan, Da (Frontiers in Aging Neuroscience, 2023)
Objective The present study aimed to explore the combined associations of depression and cognitive impairment with functional disability and mortality, and whether the joint effects of depression and cognitive impairment on mortality were influenced by functional disability. Methods A total of 2,345 participants aged 60 and above from the 2011–2014 cycle of the National Health and Nutrition Examination Survey (NHANES) were included in the analyses. Questionnaires were used to evaluated depression, global cognitive function and functional disability (including disability in activities of daily living (ADLs), instrumental activities of daily living (IADLs), leisure and social activities (LSA), lower extremity mobility (LEM), and general physical activity (GPA)). Mortality status was ascertained up to December 31, 2019. Multivariable logistic regression was performed to investigate the associations of depression and low global cognition with functional disability. Cox proportional hazards regression models were conducted to evaluate the effect of depression and low global cognition on mortality. Results Interactions between depression and low global cognition were observed when exploring associations of depression and low global cognition with IADLs disability, LEM disability, and cardiovascular mortality. Compared with normal participants, participants with both depression and low global cognition had the highest odds ratios of disability in ADLs, IADLs, LSA, LEM, and GPA. Besides, participants with both depression and low global cognition also had the highest hazard ratios of all-cause mortality and cardiovascular mortality, and these associations remained after adjusting for disability in ADLs, IADLs, LSA, LEM, and GPA. Conclusion Older adults with both depression and low global cognition were more likely to have functional disability, and had the highest risk of all-cause mortality and cardiovascular mortality.